Synthesis of reduced graphene oxide/cobalt ferrite composite particles and their magnetorheological characteristics - Yu Zhen Dong; Hyoung Jin Choi (AIP Advances, 2021)
The reduced graphene oxide/cobalt ferrite (rGO/Co-Fe) magnetic composite particle was synthesized via a solvothermal process and employed as the magnetorheological (MR) material. The morphology of rGO/Co-Fe was observed by SEM, the chemical structure was confirmed by FT-IR, and the rheological properties of rGO/Co-Fe when suspended in silicone oil were studied by a rotational rheometer under different magnetic field strengths. Along with shear stress curves of rGO/Co-Fe based MR fluid tested in a controlled shear rate mode, their magnetic field strength-dependent yield stresses were observed to fit the universal yield stress function well.